2017
DOI: 10.3892/mmr.2017.7438
|View full text |Cite
|
Sign up to set email alerts
|

Isolated chromosome 8p23.2-pter deletion: Novel evidence for developmental delay, intellectual disability, microcephaly and neurobehavioral disorders

Abstract: The current study presents a patient carrying a de novo ~6 Mb deletion of the isolated chromosome 8p23.2-pter that was identified with a single-nucleotide polymorphism array. The patient was characterized by developmental delay (DD)/intellectual disability (ID), microcephaly, autism spectrum disorder, attention-deficit/hyperactivity disorders and mildly dysmorphic features. The location, size and gene content of the deletion observed in this patient were compared with those in 7 patients with isolated 8p23.2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 45 publications
2
26
0
1
Order By: Relevance
“…Moreover, craniofacial abnormalities like microcephaly, high and narrow forehead, epicanthal folds, high arched palate, and low set ears. Furthermore, congenital heart defects (atrioventricular defects, septal defects, and pulmonary stenosis) and congenital diaphragmatic hernia [ 7 , 8 ]. We believe that the partial trisomy 13q with the concomitant partial monosomy 8p is the cause of the multiple dysmorphic features and the novel clinical presentation, e.g., pyloric stenosis, pelvic-ureteral junction stenosis, hydronephrosis, lung sequestration, and the global developmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, craniofacial abnormalities like microcephaly, high and narrow forehead, epicanthal folds, high arched palate, and low set ears. Furthermore, congenital heart defects (atrioventricular defects, septal defects, and pulmonary stenosis) and congenital diaphragmatic hernia [ 7 , 8 ]. We believe that the partial trisomy 13q with the concomitant partial monosomy 8p is the cause of the multiple dysmorphic features and the novel clinical presentation, e.g., pyloric stenosis, pelvic-ureteral junction stenosis, hydronephrosis, lung sequestration, and the global developmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…Several dozen individuals with 8p terminal deletions of variable size have been described so far. Their common features included developmental delay/intellectual disability (DD/ID), growth retardation, microcephaly, mild dysmorphic features (bilateral epicanthal folds, upslanting palpebral fissures, and ear abnormalities), widely spaced nipples, hypospadias, congenital heart defects, congenital diaphragmatic hernia, seizures, and neurobehavioral disorders [ 32 , 33 , 34 , 35 ]. The more distal deletion 8p23.2 to 8pter has been reported as a critical region associated with DD/ID, seizures, and neurobehavioral problems (autism spectrum disorders (ASD) and attention-deficit hyperactivity disorder (ADHD)) [ 34 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Association studies have implicated Csmd protein family loss of function in the onset of cognitive decline [3,5,7,8]. This suggests that Csmd2 may function to maintain normal synaptic function in the brain.…”
Section: Csmd2 Is Enriched In Synapsesmentioning
confidence: 99%
“…A number of association studies focusing on copy number variants and single nucleotide polymorphisms have identified various novel risk factors for psychiatric disorders. Deletions in members of the Cub and Sushi Multiple Domains (CSMD) gene family have been implicated in the occurrence of ASD, schizophrenia, and other neurodevelopmental disorders associated with deficits in cognitive ability and alterations in behavior [3][4][5][6][7]. While recent studies on the CSMD family focus on CSMD1, little is known about the other members of the family, CSMD2 and CSMD3.…”
Section: Introductionmentioning
confidence: 99%